Ribosome Biogenesis in Archaea - Londei, Paola; Ferreira-Cerca, Sébastien (Frontiers in Microbiology, 2021)
Making ribosomes is a major cellular process essential for the maintenance of functional ribosome homeostasis and to ensure appropriate gene expression. Strikingly, although ribosomes are universally conserved ribonucleoprotein complexes decoding the genetic information contained in messenger RNAs into proteins, their biogenesis show an intriguing degree of variability across the tree of life. In this review we summarize our knowledge on the least understood ribosome biogenesis pathway: the archaeal one. Furthermore, we highlight some evolutionary conserved and divergent molecular features of making ribosomes across the tree of life.